THE INFLUENCE OF LEADERSHIP STYLE, JOB SATISFACTION, AND WORK ENGAGEMENT ON TURNOVER INTENTION (STUDIES ON EMPLOYEES OF PT OLAM INDONESIA, JAKARTA) - Mardian Dwiswara, Mas Ghea; Andyan Pradipta Utama (Dinasti International Journal of Management Science, 2022)
This study analyzes how leadership style, job satisfaction, and work engagement influence employee turnover intention at PT Olam Indonesia. The research object is employees of PT Olam Indonesia. This quantitative descriptive research was conducted on 145 respondents. Slovin formula was used to obtain a total sample of 106 employees. Survey was used as data collection method and questionnaire as research instrument. Structural Equation Model by using the Smart-PLS analysis tool was utilized to obtain research results which prove that both leadership style and job satisfaction have significant and negative influence on turnover intention.